Examining associations of folic acid supplements administered to mothers during pre-conceptional and prenatal periods with autism spectrum disorders in their offspring: insights from a multi-center study in China - Jiang, Yan; Guo, Cuihua; Kuang, Min; Lin, Lizi; Xu, Guifeng; Pan, Ning; Weng, Xuchu; Jing, Jin; Shi, Lei; Yi, Quanying; Wang, Xin (Frontiers in Public Health, 2024)
Objective To investigate the relationship between maternal folic acid (FA) supplementation during the pre-conceptional and prenatal periods and the subsequent risk of autism spectrum disorder (ASD) in offspring. Methods A total of 6,049 toddlers aged 16–30 months were recruited from August 2016 to March 2017 for this cross-sectional study conducted in China. The parents of the enrolled toddlers provided information on maternal supplemental FA, socio-demographic information, and related covariates. Standard diagnostic procedures were implemented to identify toddlers with ASD. Results Among the 6,049 children included in the study, consisting of 3,364 boys with an average age of 22.7 ± 4.1 months, a total of 71 children (1.2%) were diagnosed with ASD. Mothers who did not consume FA supplements during the prenatal period were found to have a significantly increased risk of having offspring with ASD, in comparison to those who were exposed to FA supplements (odds ratio [OR] = 2.47). However, we did not find a similar association during the pre-conceptional period. Compared to mothers who consistently used FA supplements from pre-conception to the prenatal period, those who never used FA supplements were statistically significantly associated with a higher risk of ASD in their offspring (OR = 2.88). Conclusion This study indicated that providing continuous maternal FA supplementation during the pre-conceptional and prenatal periods may decrease the risk of ASD in offspring. The prenatal period is considered to be the most crucial time for intervention.